1985
DOI: 10.1007/bf00432232
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic effects of enalapril maleate in normal volunteers

Abstract: In order to establish any psychotropic effects of the angiotensin-converting enzyme inhibitor enalapril, the drug was administered in doses of 20 mg every morning for 14 days to 12 normal subjects, and compared with placebo on a battery of physiological, psychological and subjective tests, before and after the dose on the 1st and 14th days. Diastolic blood pressure was significantly reduced and heart-rate increased by enalapril as compared with placebo; one component (P1-N1) of the auditory evoked EEG response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…Angiotensin-converting enzyme inhibitors like enalapril reduce blood pressure by a mechanism unrelated to that of 1-adrenoceptor blockers. The possible central effects of these drugs have not yet been evaluated, although in a recent study it was found that they enhanced attention and alertness (Olajide & Lader, 1985).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Angiotensin-converting enzyme inhibitors like enalapril reduce blood pressure by a mechanism unrelated to that of 1-adrenoceptor blockers. The possible central effects of these drugs have not yet been evaluated, although in a recent study it was found that they enhanced attention and alertness (Olajide & Lader, 1985).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…In 12 normal volunteers, enalapril had no effect on mood compared with placebo [25]. However, psychomo tor ability (as measured by tapping rate), alertness, and attention were enhanced.…”
Section: Depression and Maniamentioning
confidence: 90%
“…There have been repeated reports in the literature of impairment of central nervous function, including memory (Solomon et al, 1983) and sleep (Betts & Alford 1985), following treatment with 13-adrenoceptor blockers, but there have been few studies with ACE inhibitors to assess their CNS activity. Olajide & Lader (1985) have, however, reported increased attention and alertness with enalapril. The aim of this study was to investigate under controlled conditions, some central nervous effects of the newly developed ACE inhibitor cilazapril as compared with the P-adrenoceptor blocker metoprolol and placebo.…”
Section: Introductionmentioning
confidence: 93%